2016
DOI: 10.1016/j.yjmcc.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The TGF-β pathway mediates doxorubicin effects on cardiac endothelial cells

Abstract: Elevated ALK4/5 ligands including TGF-β2 and activins have been linked to cardiovascular remodeling and heart failure. Doxorubicin (Dox) is commonly used as a model of cardiomyopathy, a condition that often precedes cardiovascular remodeling and heart failure. In 7-8-week-old C57Bl/6 male mice treated with Dox we found decreased capillary density, increased levels of ALK4/5 ligand and Smad2/3 transcripts, and increased expression of Smad2/3 transcriptional targets. Human cardiac microvascular endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 86 publications
(78 reference statements)
2
24
0
Order By: Relevance
“…Several mechanisms have been suggested to mediate DOXinduced toxicity to cardiomyocytes (4,25), whereas endothelial injury has received little attention (26,27). In our experiments, the apoptosis-associated DNA fragmentation was observed approximately to the same extent in cardiomyocytes and ECs.…”
Section: Discussionsupporting
confidence: 53%
“…Several mechanisms have been suggested to mediate DOXinduced toxicity to cardiomyocytes (4,25), whereas endothelial injury has received little attention (26,27). In our experiments, the apoptosis-associated DNA fragmentation was observed approximately to the same extent in cardiomyocytes and ECs.…”
Section: Discussionsupporting
confidence: 53%
“…TGF-β is associated with Dox-induced cardiotoxicity (36). In the cardiovascular system, TGF-β is involved in fibrotic cardiac remodeling, and a previous study suggested that inhibition of the TGF-β pathway alleviates left ventricular remodeling and systolic and diastolic dysfunction, thus alleviating the detrimental effects of Dox on endothelial cells (37). It has also been demonstrated that the inhibition of TGF-β attenuates diastolic dysfunction by reducing cardiac fibrosis in a model of anthracycline-induced cardiomyopathy (38).…”
Section: Discussionmentioning
confidence: 99%
“…A potential reason for the reduction in pro-MMP 2 over time is related to the high concentration of TIMP 4 within the cardiac tissue, contributing to the regulation of its integrity and decreasing MMP-induced capillary permeability similarly to what was formerly demonstrated in clinical conditions that damage the blood-brain barrier (Rosenberg et al 1998). Besides the inhibition of MMPs enzyme activity by TIMPs, it must be emphasized that MMPs activity is a complex process that also comprises regulation of MMPs gene expression, which can be inhibited by TGF-β whose pathway is known to be involved in doxorubicin-induced cardiovascular remodeling, as well as the regulation of MMPs enzyme activity by "switch" mechanism (Papazafiropoulou & Tentolouris 2009, Sun et al 2016.…”
Section: Discussionmentioning
confidence: 59%